1993
DOI: 10.1016/0168-1702(93)90078-2
|View full text |Cite
|
Sign up to set email alerts
|

A H1 hemagglutinin of a human influenza A virus with a carbohydrate-modulated receptor binding site and an unusual cleavage site

Abstract: Two receptor binding variants of the influenza virus A/Tübingen/12/85 (H1N1) were separated by their different plaque formation in MDCK cells. Hemagglutination of variant I was restricted to red blood cells of guinea pigs, whereas variant II also hemagglutinated chicken cells. The variants differed also in their ability to bind to alpha 2,6-linked sialic acid. Evidence is presented that this difference is determined by a complex carbohydrate side chain at asparagine131 near the receptor binding site which is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 45 publications
1
15
0
1
Order By: Relevance
“…The HA of LPAI viruses is activated at the monobasic cleavage site, that is usually an arginine but sometimes a lysine [94,95], by proteases that are present only in respiratory or intestinal epithelial tissues. Infection is therefore restricted to these organs.…”
Section: H D Klenk Et Almentioning
confidence: 99%
“…The HA of LPAI viruses is activated at the monobasic cleavage site, that is usually an arginine but sometimes a lysine [94,95], by proteases that are present only in respiratory or intestinal epithelial tissues. Infection is therefore restricted to these organs.…”
Section: H D Klenk Et Almentioning
confidence: 99%
“…Glycans near antigenic peptide epitopes interfere with antibody recognition (12), and glycans near the proteolytic activation site of HA modulate cleavage and influence the infectivity of influenza virus (13). Mutational deletion of HA glycosylation sites can affect viral receptor binding (14). Our analysis of HA sequences revealed that the peptide sequences around the glycosylation sites are highly conserved (Fig.…”
mentioning
confidence: 95%
“…Amino acid sequence comparisons between naturally occurring avirulent and virulent avian influenza viruses have shown that HAs with restricted cleavability (avirulent type) usually have a single arginine (R) whereas those with high cleavability (virulent type) have multiple basic residues situated immediately upstream of the cleavage site (17) ( Table 3). The majority of influenza A viruses have R at the carboxyl terminus of HA1 and glycine (G) at the amino terminus of HA2, although some have lysine (K) at the former position (63,93). Among H5 viruses, proline (P) and glutamine (Q), located proximally upstream of the HA1 carboxyl terminus, are also conserved.…”
Section: Sequence Requirement For High Hemagglutinin Cleavability Andmentioning
confidence: 99%